Synthesis of biochar from fronds palm waste as a support for CaO catalyst - Vito Oktariandi; Zuchra Helwani; Irfan Sarhadi Akbar; Muhammad Dian Rizky; Putri Anjani; Rendy Putra Perdana; Amun Amri (Universitas Lambung Mangkurat, 2024)
Production palm oil-based biodiesel production itself has been widely developed in Indonesia to replace fuel because the palm oil commodity has the greatest potential for biodiesel for biodiesel production. The use of catalysts affects the production of biodiesel because it can accelerate the production of biodiesel which is needed. Materials that has the potential to be part of the catalyst is activated carbon from palm frond waste palm. Palm frond waste has great potential and is supported by its lignocellulosic component. lignocellulose component, so it can be utilized as activated carbon. Research This research has variations in the procedure, namely pyrolysis temperature variations of 450°C and 500°C, pyrolysis time of 15 minutes and 20 minutes as well as the base used in impregnation, namely NaOH and KOH. The catalyst that has been The synthesized catalyst was characterized using XRD and BET analysis. XRD testing XRD testing obtained the smallest particle size on the 500°C CaO/NaOH/Biochar catalyst with a pyrolysis time of 15 minutes amounting to 26.925732 nm and in the BET test, the smallest particle size was obtained. BET testing obtained the largest catalyst surface area on CaO/NaOH/Biochar catalyst 500°C with pyrolysis time of 15 minutes amounted to 8.1626 m2/g.